PA.48 Expected and Unexpected Term Admissions to Neonatal Intensive Care (NICU). (9th June 2014) - Granger, C; Okpapi, A; Peters, C; Campbell, M
Abstract : Background: Admission of babies to NICU for medical care involves the separation of mothers and babies. We questioned what proportion of term babies were admitted in our institution and what interventions they required. Methods: We retrospectively reviewed the NICU database to identify all babies ≥ 37 weeks gestation admitted to our tertiary level service over a 12 month period. We classified term admissions as "expected" when NICU admission was anticipated following an antenatal diagnosis or "unexpected" where there were no concerns. Demographic data were collected for all babies and the source of admission, diagnosis, interventions and length of stay (LoS) documented. Results: There were 5843 babies delivered over the 12 month period of whom 4900 (83.9%) were ≥ 37 weeks. There were 453 (9.2%) term babies admitted to NICU; 65 (14%) of these admissions were expected and 389 (8%) unexpected. Median length of stay was 3 days. 173 (44.5%) of the unexpected admissions had a LoS <24 hrs in duration. Of these babies 105 were discharged or transferred within 6 h. 11/105 babies required medical intervention prior to transfer for cardiac or surgical management. The remaining 94 were discharged to postnatal ward, 22/94 received IV antibiotics, no other interventions were required. Conclusion: 9.2% of term infants were admitted to NICU. A significant proportion of "unexpected" admissions had a brief NICU stay and received minimal intervention. Development of ward based observation facilities has the potential to reduce NICU admissions in this group of term babies.